CONTRIBUTION A LA MULTIPLICATION, PAR GRAINES ET PAR BOUTURAGE DE SEGMENTS DE TIGES ET DE RACINES, DE TROIS FRUITIERS SPONTANES DE LA REGION DES SAVANES AU TOGO : HAEMATOSTAPHIS BARTERI HOOK. F., LANNEA MICROCARPA ENGL. & K. KRAUSS ET SCLEROCARYA BIRREA - Agbogan, Akouèthê; Bammite, Damigou; Tozo, Koffi; Akpagana, Koffi (European Scientific Journal, ESJ, 2014)
Introduction: The present work focused on the multiplication by seeds and cuttings of H. barteri, L. microcarpa, and S. birrea, three spontaneous fruit trees in decrease in Togo. Material and methods: Seeds and cuttings were taken from the savannas region in Togo. The multiplication essays were conducted in the laboratory and greenhouse in the University of Lomé. Germination essays were conducted using distilled water soaking, sulfuric acid treatment or mechanical scarification. Propagation by cuttings essays were conducted in greenhouse on soil taken from the Botany garden of the University of Lomé or sea sand previously treated with sulfuric acid and thoroughly rinsed with distilled water in presence of ¼ diluted Hoagland solution added with or not of IAA. Results: H. barteri seeds showed a low germination rate: 10% for freshly harvested seeds, 23% for seeds conserved for three months and 8% for one year seeds. L. microcarpa seeds sprout at 82% during the first week of harvest and lost viability about 14 weeks after harvest. For S. birrea germination rate increased from 50.12% when harvested to 69.18% and 74.6% for respectively 3 and 12 months after harvest and room conservation. For propagation using cuttings, only S. birrea was capable of multiplication in our essay conditions with a success rate of root cuttings of 71% for adult plants and 79.28 % for young plants. Conclusion: these results constituted very precious tools for production program of these 3 fruit trees for their sustainable conservation.